Teaching methods and oral ability of upper primary pupils in English language in selected primary schools in Lira District : a study - Orech-Wange, James M. (Kampala : Makerere University, 1993)
Thesis (M.Ed.) - Makerere University, 1993.
Includes bibliographical references: (p.79-83)
Keywords: English language -- Study and teaching (Elementary) -- Uganda -- Lir a District